Construction and Structural Analysis of Forced Vibration Generating Mechanism in Chisel-Cultivator (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
It is dedicated to the theoretical research of the construction and structural analysis of the mechanism that generates forced vibration in the chisel-cultivator. As a result of research, the constructive and kinematic scheme of the mechanism generating forced vibrations was developed, and the optimal values of the dimensions of its working bodies were determined.